Effectiveness of Partial and Adjustment Neostigmine Dose as a Neuromuscular Reversal for Single Dose Rocuronium - Hidayat, Jefferson; Marsaban, Arif HM; Daryono, Maria Veronica Tita Ekaputri Hadi (Bali Journal of Anesthesiology, 2018)
Background: Routine reversal (neostigmine) and the use of quantitative monitoring of neuromuscular blockade (Train of Four Ratio (TOFR)) are recommended to prevent the occurrence of residual paralysis. This study attempted to determine the effectiveness between neostigmine partial dose 0.02 mg/kgbw and adjusted dose based on TOFR value in recovering neuromuscular blockade of single dose rocuronium 0.6 mg/kgbw.Methods: This randomized clinical trial was performed in the operating room of Integrated Surgical Care Unit of Cipto Mangunkusumo General Hospital and Kirana Clinic. Sixty-one patients who underwent elective surgery in general anesthesia were randomized in to 2 groups: administration of neostigmine in partial dose 0.02 mg/kgbw (group A) and adjusted dose based on TOFR value (group B). Quantitative monitoring evaluation of neuromuscular blockade was performed four times: after adequate spontaneous breathing, 5, 10, and 15 minutes after reversal.Result: The mean of TOFR values in group A and group B respectively: after spontaneous breathing 42% and 50% (p=0.436); 5 minutes after reversal 80.2% and 89.2% (p=0.083); 10 minutes after reversal 92.2% and 94% (p=0.399); 15 minutes after reversal 94.3% and 94.9% (p=0.526). After the 5 minutes of reversal, group B (80.6%) reaches TOFR value â¥ 90% many more than group A (63.3%) (p=0.132).Conclusion: Neostigmine partial dose 0.02 mg/kgbw was as effective as administering neostigmine in adjustment dose based on TOFR values to achieve complete recovery from the neuromuscular block effect of single-dose rocuronium 0.6 mg/kgbw. This study also show the complete recovery of neuromuscular block when TOFR value â¥ 90%.